2013
DOI: 10.1182/blood-2013-01-478222
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of miR-155 in individuals with monoclonal B-cell lymphocytosis and patients with B chronic lymphocytic leukemia

Abstract: • miR-155 levels are significantly and increasingly overexpressed as normal B cells progress to MBL and to CLL.• Plasma levels of miR-155 before treatment were significantly lower in patients with CLL who experienced complete response than in all others.Noncoding RNAs play a pivotal role in the pathogenesis of chronic lymphocytic leukemia (CLL). We hypothesized that microRNAs (miRs) are involved in the transition from monoclonal B-cell lymphocytosis (MBL) to CLL and tested miR-15a/ 16-1 cluster, miR-21, and mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
157
2
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 187 publications
(175 citation statements)
references
References 40 publications
7
157
2
2
Order By: Relevance
“…These findings suggest that miR‐21 might function as a biomarker for the diagnosis of DLBCL. Our previous studies showed that miR‐155 was significantly overexpressed in monoclonal B‐cell lymphocytosis (MBL) when compared with normal B cells and that miR‐155 overexpression in plasma is a predictor of poor response to therapy (Ferrajoli et al ., 2013). Similar studies have reported that miR‐150 and miR‐342 were significantly downregulated in the plasma of acute myeloid leukemia (AML) patients at diagnosis compared to healthy controls and that these microRNAs are candidate biomarkers and potential predictors of relapse in AML (Fayyad‐Kazan et al ., 2013).…”
Section: Circulating Mirnas As Biomarkersmentioning
confidence: 99%
“…These findings suggest that miR‐21 might function as a biomarker for the diagnosis of DLBCL. Our previous studies showed that miR‐155 was significantly overexpressed in monoclonal B‐cell lymphocytosis (MBL) when compared with normal B cells and that miR‐155 overexpression in plasma is a predictor of poor response to therapy (Ferrajoli et al ., 2013). Similar studies have reported that miR‐150 and miR‐342 were significantly downregulated in the plasma of acute myeloid leukemia (AML) patients at diagnosis compared to healthy controls and that these microRNAs are candidate biomarkers and potential predictors of relapse in AML (Fayyad‐Kazan et al ., 2013).…”
Section: Circulating Mirnas As Biomarkersmentioning
confidence: 99%
“…64 In addition, exosomal miR-21 and miR-29a were demonstrated to stimulate Toll-like receptor-7 and -8, causing a prometastatic inflammatory response and activating tumor growth and metastasis. 65 Furthermore, Ferrajoli et al 66 described an overexpression of miR-155 in free circulating and blood microvesicles for MBL (monoclonal B-cell lymphocytosis) and CLL (chronic lymphocytic leukemia) patients. Separately, in another study, 11 exosomal miRNAs were observed overexpressed in prostate cancer patients and miR-141 and miR-375 were presented as potential markers of metastatic prostate cancer based on exosomal and microvesicle samples.…”
Section: Exosomal Mirnas In Cancermentioning
confidence: 99%
“…66 For example, increased levels of exosomal miR-141 and miR-375 were capable of predicting metastasis or disease recurrence in prostate cancer. 91 Exosomal miRNAs have shown distinct profiles in ovarian cancer versus benign ovarian tumors.…”
Section: Exosomes As Novel Cancer Biomarkersmentioning
confidence: 99%
“…A number of studies have shown deregulation of exosomal-miRNA levels as a potential biomarker for cancer [150]. For example, exosomal levels of miR-141 and miR-375 can be used to predict metastasis or the recurrence of disease in prostate cancer [151].…”
Section: Liquid Biopsies-the Future?mentioning
confidence: 99%